Performance of the EQ-5D-Y Interviewer Administered Version in Young Children - Razia Amien; Desiree Scott; Janine Verstraete (MDPI AG, 2022)
(1) Background: An estimated 78% of South African children aged 9-10 years have not mastered basic reading, therefore potentially excluding them from self-reporting on health-related outcome measures. Thus, the aim of this study was to compare the performance of the EQ-5D-Y-3L self-complete to the newly developed interviewer-administered version in children 8-10 years. (2) Methods: Children (n = 207) with chronic respiratory illnesses, functional disabilities, orthopaedic conditions and from the general population completed the EQ-5D-Y-3L self-complete and interviewer-administered versions, Moods and Feelings Questionnaire (MFQ) and Faces Pain Scale-Revised (FPS-R). A functional independence measure (WeeFIM) was completed by the researcher. (3) Results: The 8-year-olds had significantly higher missing responses (x2 = 14.23, p < 0.001) on the self-complete version. Known-group and concurrent validity were comparable across dimensions, utility and VAS scores for the two versions. The dimensions showed low to moderate convergent validity with similar items on the MFQ, FPS-R and WeeFIM with significantly higher correlations between the interviewer-administered dimensions of Mobility and WeeFIM mobility total (z = 1.91, p = 0.028) and Looking After Myself and WeeFIM self-care total (z = 3.24, p = 0.001). Children preferred the interviewer-administered version (60%) (x2 = 21.87, p < 0.001) with 22% of the reasons attributed to literacy level. (4) Conclusions: The EQ-5D-Y-3L interviewer-administered version is valid and reliable in children aged 8-10 years. The results were comparable to the self-complete version indicating that versions can be used interchangeably.